Work Stress, Work Environment and Compensation on Job Satisfaction with Motivation as an Intervening Variable in Mineral Water Distributor Company: Stres Kerja, Lingkungan Kerja dan Kompensasi Terhadap Kepuasan Kerja dengan Motivasi Sebagai Variabel Intervening pada Perusahaan Distributor Air Mineral - Fauzi, Ahmad Richi; Ubaidillah, Hasan (Indonesian Journal of Innovation Studies, 2023)
This study aims to examine the effect of work stress, work environment and compensation on job satisfaction with motivation as an intervening variable. The approach used in this research is a quantitative approach. The population in this study were all employees of PT. Mago Pasific Abadi totaling 150 employees. The retrieval technique uses the accidental technique method. The sample in this study were 60 employees at PT. Mago Pasific Abadi. The data used in this study are questionnaire data and data sourced from PT Mago Pasific Abadi. Data collection techniques using questionnaires, interviews, observations, and documentation. Data analysis using SPSS Statistics Software version 23.0 The results obtained from the path analysis showed that job stress had significant effect on job satisfaction, work environment had significant effect on job satisfaction, compensation had a significant effect on job satisfaction, motivation has a significant effect on job satisfaction, job stress does have a significant effect on job satisfaction through the motivation variable as the intervening variable, the work environment does have a significant effect on job satisfaction through the motivation variable as the intervening variable